Pyrodinium bahamense and other dinoflagellate cyst distribution in surface sediments of Maqueda Bay, Samar, Philippines - Rosales, Sandre Rose C. (2017)
This study provides an assessment of the dinoflagellate cyst abundance, distribution and density in the surface sediments of Maqueda Bay, Samar. Sediment samples were collected from the twelve sampling stations using grab sampler on January 2017. Collected samples were used for analysis of grain size, moisture content, bulk density, organic content and nutrient content. Palynological technique was used for the cyst processing. Surface sediment characterization revealed that the study site was generally muddy sandy. Identification of the cyst followed after microscopic observation. Twenty-three dinoflagellate cyst species were found and identified to be under the three dinoflagellate orders: Peridiniales, Gymnodiniales, and Gonyaulacales. The cyst density of all stations ranged from 3-80 cyst g raised to negative one DW with Pyrodinium bahamense as the dominant species. P. bahamense cysts were observed in 11 stations ranging from 0-18 cysts g raised to negative one DW. Several physicochemical parameters of the surface sediments and waters such as depth, dry bulk density, organic content and nutrient content may have also influenced cyst distribution and density.